Arneroma B: structure reassignment and total synthesis - Deepak, Nashvin Mikhail Singh (2024)
The proposed structure of arneroma B has been revised from a cyclopentadienone to a 2,4-disubstituted furan. The reassignment has been confirmed by total synthesis of the revised structure.